Аналіз селективної дії природного добору за показниками плодових репродуктивних втрат - Лановенко, Олена; Lanovenko, Olena (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті проаналізовано можливість оцінки селективної дії природного добору в людських популяціях за частотою та динамікою плодових репродуктивних втрат. Показано, що популяції з різною генетико-демогра¬фічною структурою відрізняються частотою ранніх мимовільних викиднів, які мають високу спадкову компо¬ненту. На фоні зниженого ризику виникнення репродуктивних втрат у популяціях Херсонської області спосте¬рігається статистично достовірне зростання поширеності вроджених вад розвитку новонароджених. The article examines the possibility of estimating the selective action of natural selection on the population structure and dynamics of the frequency of fetal reproductive losses. In particular, the material of early miscarriages with an accurate assessment of their frequency in the entire study population may be an indicator of the intensity of selective action of natural selection in embryogenesis as a major factor causing adaptive changes in the genetic structure of populations. Shown that populations with different genetic and demographic structure differ in the frequency of early spontaneous abortions, with a high hereditary component. In the populations of the Kherson region in the structure of reproductive losses 56,47 % were spontaneous abortions with a predominance of abortions up to 12 weeks of gestation (40,71 %), 21,41 % − abortion for medical reasons, 22,12 % − stillbirth. Abortion rate was 21,68 per 1000 registered pregnancies, including miscarriages before 12 weeks of gestation − 14,02 ‰. Rate of reproductive loss and its components differ in rural and urban populations. The total frequency of reproductive losses during the years of research in rural populations was 41,05 ‰ and was significantly higher (χ2 = 24,1), than in the city of Kherson (29,86 ‰) due to the relatively high frequency of spontaneous abortions (27,11 ‰) in particular the first trimester miscarriages (15,18 ‰), for medical abortions (7,64 ‰). Reducing the population frequency of reproductive losses accompanied by a statistically significant increase in the population prevalence of congenital malformations that can be attributed to a selective effect "screening" selection in utero.
Analysis of the Selective Action of Natural Selection in Terms of Fetal Reproductive Losses
Keywords: мимовільні викидні ранніх термінів гестації; популяційно-генетичний моніторинг; при¬родний добір; population genetic monitoring; miscarriages early gestation; natural selection